RULA-Based Ergonomic Assessment of Sitting Posture as a Risk Factor for Neck Pain in Students - Septadina, Indri Seta; Wardiansah; Suciati, Tri; Adnindya, Msy Rulan; Putri, Sima Asmara Dewa Marya Mahardika; Legiran; Malahayati, Putri; Odiesta, Muhammad Ramadhan; Hasbi, Alfian (Utan Kayu Publishing, 2025)
Research on ergonomic risk factors for neck pain among Islamic boarding school students remains scarce, despite their prolonged study and Qur’an memorization activities in static sitting postures. Non-neutral body posture during learning may increase the risk of musculoskeletal disorders (MSDs), particularly neck pain, which can impair concentration and quality of life. This analytic cross-sectional study aimed to assess students’ body posture during study and memorization activities and to examine its association with neck pain. A total of 72 boarding and non-boarding students participated. Data were collected using questionnaires and the Rapid Upper Limb Assessment (RULA), and analyzed with chi-square tests and logistic regression to obtain prevalence ratios (PR) and p-values. Neck pain was reported by 63.9% of respondents; 72.2% exhibited poor sitting posture, and 80.6% reported moderate-to-severe stress. Bivariate analysis showed a significant association between stress level and neck pain (p = 0.033; PR = 2.19; 95% CI: 1.25–3.83). In multivariate logistic regression, no variable reached conventional statistical significance; however, students with moderate-to-severe stress had a 3.81-fold higher risk of neck pain (p = 0.057). These findings underscore the need for integrated ergonomic and psychosocial interventions in Islamic boarding school settings to reduce neck pain risk among students.